EFFICIENCY OF THE ANTIMICROBIAL AGENTS WITH COMBINATION OF LOW LEVEL LASER RADIATION ON CLINICAL STRAINS OF STAPHYLOCOCCUS AUREUS ISOLATED IN DISEASES OF THE ORAL CAVITY - Panas, M.A.; Kyryk, C.A.; Vilhova, I.V.; Panas, M.I. (World of Medicine and Biology, 2015)
The aim of our research was examine the effectiveness of the combined use of antibacterial drugs and low-level laser radiation on Staphylococcus aureus in parodontitis. Materials and methods: We examined the age group 30-55 years of 40 people with parodontitis. Allocated 12 strains of S. aureus and the reference strain S. aureus ATCC 25923 (F-49) was used to examine the effect of laser radiation, when used in conjunction with antibacterial agents for 5 min. and without of laser radiation.Results: According to received data found that the complete inhibition of growth of isolates was observed. With respect to the application of penicillin S. aureus, isolated from patients with parodontitis, the number of microbial cells was germinated (16,0±2,6) CFU/ml. When are using amoxicillin/clavulanate recorded a slight decrease in the level of quantitative seeding S. aureus. Thus, the figure of parodontitis (16,6±3,1) CFU/ml (p
Keywords: low-level laser radiation; parodontitis; antibacterial drugs; S. Aureus